Cardiopulmonary resuscitation duration and survival in out-of-hospital cardiac arrest patients. (February 2017) - Adnet, Frederic; Triba, Mohamed N.; Borron, Stephen W.; Lapostolle, Frederic; Hubert, Hervé; Gueugniaud, Pierre-Yves; Escutnaire, Josephine; Guenin, Aurelien; Hoogvorst, Astrid; Marbeuf-Gueye, Carol; Reuter, Paul-Georges; Javaud, Nicolas; et al.
Abstract: Aim: Relationship between cardiopulmonary arrest and resuscitation (CPR) durations and survival after out-of-hospital cardiac arrest (OHCA) remain unclear. Our primary aim was to determine the association between survival without neurologic sequelae and cardiac arrest intervals in the setting of witnessed OHCA. Methods: We analyzed 27, 301 non-traumatic, witnessed OHCA patients in France included in the national registry from June 1, 2011 through December 1, 2015. We analyzed cardiac arrest intervals, designated as no-flow (NF; from collapse to start of CPR) and low-flow (LF; from start of CPR to cessation of resuscitation) in relation to 30-day survival without sequelae. We determined the influence of recognized prognostic factors (age, gender, initial rhythm, location of cardiac arrest) on this relation. Results: For the entire cohort, the area delimited by a value of NF greater than 12 min (95% confidence interval: 11–13 min) and LF greater than 33 min (95% confidence interval: 29–45 min), yielded a probability of 30-day survival of less than 1%. These sets of values were greatly influenced by initial cardiac arrest rhythm, age, sex and location of cardiac arrest. Extended CPR duration (greater than 40 min) in the setting of initial shockable cardiac rhythm is associated with greater than 1% survival with NF less than 18 min. The NF interval was highly influential on the LF interval regardless of outcome, whether return of spontaneous circulation (p < 0.001) or death (p < 0.001). Conclusion: NF duration must be considered in determining CPR duration in OHCA patients. The knowledge of (NF, LF) curves as function of age, initial rhythm, location of cardiac arrest or gender may aid in decision-making vis-à-vis the termination of CPR or employment of advanced techniques.